Recovering place : reflections on Stone Hill - Taylor, Mark C., 1945- (Religion, culture, and public life., 2014)
Indescribable ... it contains some of the finest prose and photography you'll find anywhere. A weird, wonderful, wallop-packing work of untethered spirituality. Beautiful images of the natural world paired with introspective musings on life's greatest mysteries fill this wondrous compendium ... Recovering Place makes an excellent and unforgettable giftbook nature lovers especially will enjoy browsing its insights. [Taylor's] musings, when paired with the author's own color photos, read as poetic and verbal artifacts ... The book will inspire readers to pause, look, and consider. Thomas Krens, director emeritus, Solomon R. Guggenheim Foundation New York:Taylor has created a work that is simultaneously stunningly direct and sensually complex. Its natural, spatial, analytical and temporal dimensions combine to perhaps surpass even his most brilliant and well reasoned texts in its capacity to draw the viewer/reader into a visceral and theoretical discourse at the very same moment. Recovering Place is about time, the ceaseless contemplation of which is at the root of all of Taylor's work. The originality of both his art and his writing are drawn together in this beautifully elegant book, which will, without doubt, generate pilgrimages to 'the Place.' Steven Holl, architect:One of our most important philosophers of culture, Taylor frames his poetic and passionate argument with a very personal reflection, not unlike Thoreau. Stone Hill, Taylor's Walden Pond, gives a visual identity to his important words. His poetic manifesto of place is a joy to read its timely urgency is a gift to students in philosophy, art, architecture, and cultu.